Festival Menongkah: Revitalisasi Budaya dan Bahasa Duanu Menuju Industri Kreatif - Dessy Wahyuni (Balai Arkeologi Maluku, 2017)
The life of the Malay Duanu community, a remote indigenous community, is started to be exposed recently. Their existence is recognized by the world through the Menongkah Festival that has achieved the MURI record twice. Unfortanely, following the current globalization progress, the expose of this ethnic group starts to erodes their culture and language toward extinction. It is unfortunate as wel that this activity only highlight the ceremonial part. In fact, Duanu people can take advantage of this Menongkah Festival as a medium for the revitalization of Duanu language and culture. If the festival is managed well, then it is believed that this activity will be able to support the emergence of a creative economy that improves the welfare of its supporting community, as well as to revitalize their culture and language. The government should be able to create policies that capable to support the creation of locality-based creative mindset, systems, and practices of the creative industry and to keep prioritizing the existing cultural values. Therefore, through ethnographic methods, the aim of this paper is to offer the model of creative industries based on culture and language of Duanu. If Menongkah Festival is optimally utilized by developing creative undustries, it is believed that the endangered language and culture of Duanu cen be revitalized and people’s live will be more prosperous.Kehidupan masyarakat Melayu Duanu, sebuah komunitas adat terpencil saat ini mulai mengemuka. Eksistensi mereka diakui dunia melalui Festival Menongkah yang mendapatkan rekor MURI sebanyak dua kali. Namun tanpa disadari, seiring arus globalisasi yang menerpa, mengemukanya suku ini mengikis budaya dan bahasa Duanu secara perlahan ke arah kepunahan. Selain itu sangat disayangkan, kegiatan ini hanya menyorot kemeriahan sesaat. Padahal masyarakat Duanu bisa memanfaatkan Festival Menongkah ini sebagai media revitalisasi budaya dan bahasa Duanu. Apabila dikelola dengan baik, diyakini, kegiatan ini akan dapat menjadi penopang munculnya ekonomi kreatif yang meningkatkan kesejahteraan masyarakat pendukungnya, sekaligus dapat merevitalisasi budaya dan bahasa mereka. Pemerintah seharusnya dapat membuat kebijakan yang mampu mendukung terciptanya pola pikir, sistem, dan praktik industri kreatif berbasis lokalitas dan tetap mengedepankan nilai-nilai kultural yang ada. Dengan demikian, melalui metode etnografis, tulisan ini bertujuan menawarkan model industri kreatif berbasis budaya dan bahasa Duanu. Jika Festival Menongkah dimanfaatkan secara maksimal dengan mengembangkan industri kreatif, diyakini bahasa dan budaya Duanu yang nyaris punah dapat terevitalisasi serta kehidupan masyarakat pun semakin makmur.